Investigation of low‐cost dual port co‐rotating dual rotor field excited flux switching generator for low‐power rooftop wind turbine integrated with multi‐port DC micro grid - Wasiq Ullah; Faisal Khan; Shahid Hussain; Fahad Alturise (IET Renewable Power Generation, 2022)
Abstract In this paper, a novel low‐cost dual port dual rotor‐field excited flux switching generator (DPDR‐FEFSG) is proposed for low power rooftop wind turbine integrated with DC‐micro‐grids. The proposed DPDR‐FEFSG incorporated inner/outer machine to design a dual rotor structure with dual output port. Due to the existence of field excitation in DPDR‐FEFSG, overall machine cost is reduced and offered excellent flux regulation capabilities. Furthermore, single tooth non‐overlapped armature winding and toroidally wounded field winding significantly shorten end winding that reduces copper losses. Additionally, compared with the existing single‐bus DC‐micro grids system, the proposed DPDR‐FEFSG exhibits two‐port output which makes it feasible for low‐voltage (12–24 V) and high‐voltage (48 V) applications connected to the DC micro‐grids without the requirements of extra power electronics circuitry. The proposed DPDR‐FEFSG is investigated under variable field excitation and variable rotor speed. In order to achieve the desired voltage level at low and high port without frequency variation, AC–DC rectification is employed. Analysis reveals that proposed DPDR‐FEFSG offers dual output port from inner and outer machines. This dual port makes it feasible for wind turbine integrated to multi‐port DC micro‐grids. Due to availability of different voltages at various ports, different load classes are incorporated without the requirements of extra power electronics circuitry and thus reduce overall cost. Finally, a prototype is built and tested to confirm the validity of the proposed concept and finite element analysis (FEA) results.